Effect of Shenfu injection on lipopolysaccharide (LPS)-induced septic shock in rabbits. (24th April 2019) - Liu, Xi; Liu, Runzhe; Dai, Zhenfeng; Wu, Hao; Lin, Ming; Tian, Fang; Gao, Zeyu; Zhao, Xin; Sun, Yi; Pu, Xiaoping
Abstract: Ethnopharmacological relevance: Shenfu injection is a popular Chinese herbal formula that has been widely used in the treatment of shock in China. Aim of the study: To investigate the effect of Shenfu injection on lipopolysaccharide (LPS)-induced septic shock in rabbits. Materials and methods: We established a septic shock model in rabbits by administering an intravenous injection of 0.6 mg/kg LPS to anesthetized rabbit, and 15 min after LPS challenge, the rabbits were intravenously administered the Shenfu injection. In these in vivo experiments, the jugular vein of the rabbits was cannulated for LPS and drug administration, and the right common carotid artery was cannulated to record the mean arterial pressure (MAP) over a 6-h period. In addition, various serum biochemical parameters, including lactate dehydrogenase (LDH), aspartate aminotransferase (AST), glutamate transaminase (ALT), creatinine (Cre), and urea nitrogen (Urea), were measured at 0, 3, and 6 h. Serum LPS levels at 6 h were determined by the test kit. And histological changes in the heart, liver and kidney tissues were observed by HE staining. Furthermore, some related small molecules in the heart tissues were detected by MALDI-TOF-MSI. Results: We found that Shenfu injection can increase the MAP, decrease the serum LPS, LDH and AST levels, and improve the tissue morphology of the heart, liver and kidney in rabbits with LPS-induced septic shock. In addition, Shenfu injection can increase the contents of ATP and taurine while reducing the content of AMP in the heart tissue during septic shock. Conclusions: These results indicate that Shenfu injection exerts a protective effect on LPS-induced septic shock in rabbits. Graphical abstract: fx1